If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + 4b) = (5a + -4b) Remove parenthesis around (5a + 4b) 5a + 4b = (5a + -4b) Remove parenthesis around (5a + -4b) 5a + 4b = 5a + -4b Add '-5a' to each side of the equation. 5a + -5a + 4b = 5a + -5a + -4b Combine like terms: 5a + -5a = 0 0 + 4b = 5a + -5a + -4b 4b = 5a + -5a + -4b Combine like terms: 5a + -5a = 0 4b = 0 + -4b 4b = -4b Solving 4b = -4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4b' to each side of the equation. 4b + 4b = -4b + 4b Combine like terms: 4b + 4b = 8b 8b = -4b + 4b Combine like terms: -4b + 4b = 0 8b = 0 Divide each side by '8'. b = 0 Simplifying b = 0
| (5a+4b)=(4a-4b) | | 5(16)+w-35=7w+16-49 | | 96/y/y=4 | | 4y(y)=96 | | 1x^2-2x-48=0 | | 4-3a=29 | | 9+20x=29x | | cosx+3.8=0 | | 10p-27=7p | | 9 | | x-8+2(3x+3)=-3(x+2) | | 4=x+5x | | 7+3(3y-3)=-2(4y-8)+5y | | -3(5y-1)+3y=6(y+1) | | -2*x^3+17*x^2-40*x+16=0 | | 18+15y-23=y+4(18)+21 | | x^6+13x^5+42x^4=0 | | c+2(19)+3=19+5c-30 | | kx^2-8x+6=0 | | 9(14)+u-40=19u+14 | | 12/9=4/× | | f(x)=x^3-3x^2+4x+1 | | 72/8-3= | | 2[p-(2p+13)+8]=2(p+5) | | (5+3)x(10-6)= | | -5+9-24=x | | ×-5/4=(-7) | | x^2+(2-k)x+k=0 | | 17+3z=-3 | | (3x+7)+(2x+19)+3x=180 | | (3x+7)+(2x+19)+x=180 | | (3x+7)+(2x-19)+3x=180 |